Monoclonal Gammopathy of Renal Significance-A Rare Renal Presentation: A Review of Cases Reported - Asim Kichloo MD; Najma Nawaz MD; Jagmeet Singh MD; Michael Aljadah MD; Michael Stanley Albosta MD; Ravinder Bhanot MD (SAGE Publishing, 2020)
Monoclonal gammopathy of undetermined significance is a precursor to multiple myeloma characterized by monoclonal gammopathy without evidence of end organ damage. Some patients with clonal plasma cell disorder that do not meet the requirements for multiple myeloma have been seen to develop pathologic renal disease due to direct effects from deposition of monoclonal protein, referred to as monoclonal gammopathy of renal significance. In this article, we present a rare renal manifestation of monoclonal gammopathy of renal significance as focal segmental glomerulosclerosis.